Study on the application of brine mixing method in lithium extraction from Zabuye salt lake, Tibet - Qian Wu; Jiangjiang Yu; Jintao Zhang; Ke Zhang; Juntao Li; Deji Solange; Zhikui He; Lingzhong Bu; Zhen Nie (Scientific Reports)
Abstract With the rapid development of new energy industry, the demand for lithium resources continues to rise. The salinity-gradient solar pond (SGSP) technology is used to extract the lithium carbonate from Zabuye salt lake brine in the Tibet Plateau of China. Years of production practice proved that due to the unsatisfactory quality and insufficient amount of lithium-rich brine used to make the SGSP, the yield and grade of lithium concentrate in the solar pond has been seriously affected. In this paper, it has been investigated that the change rule of brine composition with different brine mixing ratios through the same/cross-year brine mixing laboratory experiments and the cross-year brine mixing production test. The optimal brine mixing ratio of winter concentrated brine and summer brine, the relevant operation parameters and the yield increase effect of lithium concentrate in the solar pond are obtained. The results show that the cross-year brine mixing method can not only significantly improve the yield and grade of lithium carbonate, but also alleviate the pressure of brine production in salt field. It is suggested that the SGSP technology coupled with the cross-year brine mixing method should be given priority in the production of lithium carbonate in Zabuye mining area.